Road Traffic Fatality Time Series Analysis in Dubai from 2012 To 2016 - Faisal Abdulla AlShamsi; Ebrahium Abdulla AlShamsi; Mohammed El-Sadig (Medsci Publications, 2020)
Introduction: Road traffic crashes were second cause of death in the UAE. Many traffic regulations and fines had been implemented in UAE to control the high number of road traffic crashes. Methods: This study is retrospective analytical study. We used data from road traffic crashes occurring in Dubai between 2012 and 2016. We extracted these data from Dubai Statistics Center (DSC) and Dubai Road and Transport Authority (RTA). We analysed the data using time series model by expert modeller of SPSS. Results: The Road traffic fatality in Dubai had an increasing trend over the four years of study. Also, seasonality were overserved in time series. More road traffic deaths had been occurred during March, December, July (9.83%, 9.71%, and 9.10% respectively). The Winter's additive model was recognized as a best model in forecasting the trend of fatalities. Forecasting model also showed a ascending trend of traffic road fatalities over the next 4 years. Conclusion: There was ascending trend in the study and the future 4 years. We need to investigate more about prevention measures for road traffic crashes. Also, further research is needed to study the correlation between temperature and fatal road crashes.